Partition Coefficients of Citric Acid between Aqueous Solutions and Long Chain Amines Dissolved in Various Solvents - Inci, Ismail (Asian Journal of Chemistry, 2012)
The extraction of citric acid from an aqueous solution into solutions of tri-n-octylamine and Alamine 336 in single solvents hexane, cyclohexane, toluene and methyl isobutyl ketone (MIBK) was investigated. Formation of acid amine complexes is a dominating factor in the system under consideration. Diluents were chosen from different chemical classes-polar and nonpolar-so as to examine the effect of diluents complex interactions. The partition coefficients and loading factors were calculated and interpreted from experimental results.